The Teaching of Physics through investigative activities on Newton's First Law (Research, Society and Development, 2019)
This work aims to contribute to the improvement in Physics Teaching through the methodology of Teaching by Investigation. In order to reach these objectives, studies were carried out on the construction of knowledge through the argumentation in the Teaching of Physics by Investigation, reading articles, theses, dissertations and books of the main authors on the subject. We planned and executed a Sequence of Investigative Teaching (SEI) proposal at a federal school about Newton's First Law to assess whether there was knowledge building through argumentation. The SEI has been divided into five stages that are Investigative Demonstration; Open questions; Reading Text; Open Laboratory and Systematization of Knowledge. The SEI developed in this activity has the purpose to allow the students to carry out activities in group, that develop the argumentation and the construction of the scientific knowledge, in which they have been essential in the learning process. The result obtained through the SEI made it possible to conclude that the teaching of Physics by Investigation, when well planned, arouses in the student the curiosity, the investigative spirit and consequently the construction of scientific knowledge.